Axial Spacing Effects on Rotor-Rotor Interaction Noise and Vibration in a Contra-Rotating Fan - Hengxuan Luan; Liyuan Weng; Ranhui Liu; Dongmin Li; Mingwei Wang (International Journal of Aerospace Engineering)
Because of the potential technical advantages, the contra-rotation technology has become a renewed interest in aviation and other applications. Contra-rotation increases efficiency in comparison with the single-rotor design, but this advantage is not fully harnessed. The axial spacing of two-stage contra-rotating blade rows has a significant impact on a contra-rotating fan/compressor. The results show that with a contra-rotation pattern, the strong unsteadiness of two-stage rotors is caused by the rotor-rotor interaction. The unsteadiness of rotor 1 is caused by the potential disturbance, and the upstream wake leads to the strong unsteadiness of rotor 2. With the increase of axial spacing, the rotor-rotor interaction is weakened, while unsteady features of two-stage rotor blades tend to be consistent. The acoustic and vibration effects of axial spacing are studied. It is found that the axial spacing has great influence of aerodynamic noise. The mean value of sound pressure level decreases by 17.2 dB in total when the axial spacing increased to 1.1 chord from 0.3 chord. For the accuracy of calculation, the scattering effect of the casing wall should be considered in the prediction of the noise. The axial spacing does not have obvious effects on the natural frequencies of the two-stage rotor blades but has certain effect on blade deformation.